Impact Assessment of M-Pesa on the - Waithaka, Wanjiku (My University, 2011)
Context The purpose of this research was to evaluate and assess the impact of Safaricom Ltd’s M-Pesa mobile money transfer system on the informal sector in Nairobi, Kenya. The study aimed to assess whether there was any impact of Safaricom’s MPesa mobile money transfer system on the informal sector in Kenya, specifically in Nairobi, and to determine the effect on businesses in relation to the role of banking in business. The method of data collection A questionnaire administered to respondents in the informal sector within Nairobi, Kenya was used as a basis for the study. The sample consisted of 110 respondents and each respondent was requested to answer questions based on current practice and opinions related to the use of the M-Pesa service. The key findings The study showed that with the use of M-Pesa becoming a part of the social and economic patterns of the informal sector, efficiencies in business have been improved with the costs of money handling reducing and a wide use and acceptance of the service based on specific conditions such as value mobility and atomic exchange. The use of M-Pesa has also replaced some key banking services that were previously only available in traditional banking channels. Therefore more people who wouldn’t otherwise enter the banking system have, through M-Pesa. The key message The research has shown that while mobile money transfer is a fairly new concept, the mobile telephony companies should continue to find new and iii innovative ways to turn the mobile phone into a tool for accessing savings and possibly even dispensing loans and advances. The banking industry also stands to benefit from an improved understanding of the ‘banking’ requirements of the informal sector and in turn develop products that appeal to the informal sector that are accessible via the mobile phone which has emerged as an important tool to disintermediate the existing ecosystem of banks
MBA - WBS
Keywords: Mobile banking, Kenya; Mobile money transfer, Kenya; M-Pesa, Kenya